Characteristics of GaN-based light emitting diodes with different thicknesses of buffer layer grown by HVPE and MOCVD. (23rd January 2017) - Tian, Pengfei; Edwards, Paul R; Wallace, Michael J; Martin, Robert W; McKendry, Jonathan J D; Gu, Erdan; Dawson, Martin D; Qiu, Zhi-Jun; Jia, Chuanyu; Chen, Zhizhong; Zhang, Guoyi; Zheng, Lirong; et al.
Abstract: GaN-based light emitting diodes (LEDs) have been fabricated on sapphire substrates with different thicknesses of GaN buffer layer grown by a combination of hydride vapor phase epitaxy and metalorganic chemical vapor deposition. We analyzed the LED efficiency and modulation characteristics with buffer thicknesses of 12 μ m and 30 μ m. With the buffer thickness increase, cathodoluminescence hyperspectral imaging shows that the dislocation density in the buffer layer decreases from  ̃1.3  ×  10 8 cm −2 to  ̃1.0  ×  10 8 cm −2, and Raman spectra suggest that the compressive stress in the quantum wells is partly relaxed, which leads to a large blue shift in the peak emission wavelength of the photoluminescence and electroluminescent spectra. The combined effects of the low dislocation density and stress relaxation lead to improvements in the efficiency of LEDs with the 30 μ m GaN buffer, but the electrical-to-optical modulation bandwidth is higher for the LEDs with the 12 μ m GaN buffer. A rate equation analysis suggests that defect-related nonradiative recombination can help increase the modulation bandwidth but reduce the LED efficiency at low currents, suggesting that a compromise should be made in the choice of defect density.